Susceptibility of Gastroesophageal Reflux Disease Symptoms in Medical Students: A Formative Study - Sutanto, Eviana Budiartanti; Sutanto, Luciana Budiati; Hardimarta, Fransisca Pramesshinta; Ernestia , Henrita; To , Lidwina Indra Aprilia Christiana; Tjitradinata , Cynthia; Sebong , Perigrinus Hermin (Fakultas Kedokteran Universitas Kristen Krida Wacana, 2025)
Introduction: Gastroesophageal Reflux Disease (GERD) is a common chronic health problem associated with decreased quality of life and high morbidity. Many factors, including lifestyle, eating habits, medication, and mental stress, can trigger gastroesophageal reflux disease. A medical student who experiences high pressure during their training may have a GERD issue. Hence, this study aims to investigate the correlation between risk factors and the development of GERD in medical students. Methods: We used data from a cross-sectional study conducted at Soegijapranata Catholic University, Semarang, among medical students. Participants were recruited with inclusion criteria, namely all students aged over 18 years who were willing to fill out a questionnaire voluntarily, and were not undergoing treatment for gastric ulcers or mental disorders. Two questionnaires are used: a questionnaire developed to obtain demographic characteristics and a GERDQ questionnaire. A significant relationship is considered to occur if the p-value <0.05. Result: A total of 122 students were included. Among them, 23 students, consisting of 16 (13.11%) women and 7 (5.73%) men, suffered from GERD. It was found that nine people (7.4%) consumed NSAIDs, with a p-value of 0.014. Conclusion: The prevalence of GERD among medical students is relatively high, showing a significant link between the use of NSAIDs and GERD. Practical studies are needed to tackle the issue of uncontrolled NSAID use and to promote lifestyle modifications.